The Rosa chinensis cv. Viridiflora Phyllody Phenotype Is Associated with Misexpression of Flower Organ Identity Genes - Yan, Huijun; Zhang, Hao; Wang, Qigang; Jian, Hongying; Qiu, Xianqin; Baudino, Sylvie; Just, Jeremy; Raymond, Olivier; Gu, Lianfeng; Wang, Jihua; Bendahmane, Mohammed; Tang, Kaixue (Frontiers in Plant Science, 2016)
Phyllody is a flower abnormality in which leaf-like structures replace flower organs in all whorls. Here we investigated the origin and the molecular mechanism of phyllody phenotype in Rosa chinensis cv. Viridiflora, an ancient naturally occurring Chinese mutant cultivar. Reciprocal grafting experiments and microscopy analyses, demonstrated that the phyllody phenotype in Viridiflora is not associated with phytoplasmas infection. Transcriptome comparisons by the mean of RNA-Seq identified 672 up-regulated and 666 down-regulated genes in Viridiflora compared to its closely related genotype R. chinensis cv. Old Blush. A fraction of these genes are putative homologues of genes known to be involved in flower initiation and development. We show that in flower whorl 2 of Viridiflora, a down-regulation of the floral organ identity genes RcPISTILLATA (RcPI), RcAPETALA3 (RcAP3) and RcSEPALLATA3 (RcSEP3), together with an up-regulation of the putative homologue of the gene SUPPRESSOR of OVEREXPRESSION of CONSTANS1 (RcSOC1) are likely at the origin of the loss of petal identity and leaf-like structures formation. In whorl 3 of Viridiflora, ectopic expression of RcAPETALA2 (RcAP2) along with the down regulation of RcPI, RcAP3 and RcSEP3 is associated with loss of stamens identity and leaf-like structures formation. In whorl 4, the ectopic expression of RcAP2 associated with a down-regulation of RcSEP3 and of the C-class gene RcAGAMOUS correlate with loss of pistil identity. The latter also suggested the antagonist effect between the A and C class genes in the rose. Together, these data suggest that modified expression of the ABCE flower organ identity genes is associated with the phyllody phenotype in the rose Viridiflora and that these genes are important for normal flower organs development.